Kindergarten and school as a learning environment for art. (1st March 2014) - Nevanen, Saila; Juvonen, Antti; Ruismäki, Heikki
This article focuses on kindergartens and schools as art educational environments. They were explored from three points of view: the physical environment, the social environment and the pedagogical environment created by the thinking and activities of teachers and artists. A multidimensional evaluation is used to analyse the data. (Interviews of artists and teachers (n=18), final reports (n=9), follow-up material from an art project in Helsinki beginning in 2000.) The project targeted children in kindergarten (3–6 years old) and in the first grades in school (7-9 years old) and included visual art, environmental art, literary art, drama, circus and architectural elements. School, kindergarten and the immediate surroundings offered an opportunity for a diversified cooperative achievement. The children proved to be skilful and significant members of society in carrying out their art projects.